Bank, stock market, and economic growth in Malaysia - Wong, Hock Tsen; Kok, Sook ching; Cheuk, Sharon Choy Sheung; Rem Ali Yusoff (Universiti Malaysia Sabah, 2009)
Bank plays an important role in an economy through channelling funds from savers to investors. This would generate more savings. consumptions. and investments. and resulting in greater efficiency and productivity. more output. and higher rate of economic growth. Thus, a well-developed banking system could contribute significantly to economic growth. Stock market may promote economic growth. Stock market encourages specialisation and also acquisition and dissemination of information and may reduce the costs of mobilising savings and thus facilities investment. Moreover, a well developed stock market may enhance corporate control by mitigating the principle-agent problem through aligning the interest of managers and owners. The role of financial system on economic growth, particularly bank and stock market are well documented in the empirical literature. However, most of the studies in the literature are on developed countries. In Malaysia, a few studies on the relationship between economic growth and both financial market and financial intermediary have been done previously. This study examines banking development and stock market development on economic growth in Malaysia over the period from 1970 to 2006 and a sub-period from 1970 to 1996. The results show that there is a long-run relationship among real gross domestic product (GOP) per capita, capital, labour, openness to international trade, banking development, and stock market development. An increase in capital, labour, openness to international trade, banking development or stock market development will lead to an increase in real GOP per capita. Moreover, these variables are generally found to be important in influencing real GOP per capita in the short run. There is some evidence stock market development to have a stronger impact on real GOP per capita than banking development in the long run. The results of Granger causality test show that there is some evidence that real GOP per capita Granger causes banking development and stock market development and not vice versa. On the whole, banking development and stock market development are important to economic growth in Malaysia.